Hand hygiene monitoring: Comparison between app and paper forms for direct observation. Issue 2 (10th December 2022) - Libero, Giulia; Bordino, Valerio; Garlasco, Jacopo; Vicentini, Costanza; Maria Zotti, Carla
Abstract: Healthcare‐associated infections (HAIs) are a global public health threat. Italy is one of the countries with the highest prevalence of HAI. Hand hygiene (HH) is a pillar of infection prevention and control. Monitoring HH is necessary to improve HH compliance, and direct observation is considered the gold standard. Transcription and analysis of data collected during direct observation of HH compliance with the WHO paper form are time‐consuming. We collected, during a 9‐day observation period, HH opportunities and compliance both with a smartphone application (SpeedyAudit) and with the WHO paper form. Then, we investigated the difference in the required time for data transcription and analysis between the WHO paper form and the use of the app. The difference in the required time for data transcription and analysis was significant with a mean time of 2 s using the app and about 14–54 min/day using paper form ( p  = .004) while no significant difference was found in measured compliance rates between the two data collecting methods. HH monitoring with an app is time‐saving, and the app we used was easy to use.